KORNELIUS, SANG PRIBADI TRANSISI SEBAGAI TAWARAN MODEL DIALOG - Viktorahadi, R.F. Bhanu (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2018)
Almost all of the Church in Indonesia are still regarded a foreign entity in the midst of the larger society where it stands. It comes to happen because the Indonesian Church is often considered of not willing to open herself to create a dialogue with the society. In this case, Cornelius (Acts 10:34-43) as a transition personal could perhaps become inspiration for the Church in building a sincere dialogue with her circumstances. In this conversation, the unique personality of Cornelius as a transition personal succesfully made use the elements which belong to his pagan background and his religious background as a means for doing reciprocal repentance to him and to Peter. By doing this, at the same time, Cornelius placed himself as Peter’s equal partners of dialogue. Creating a dialogue with others is indeed a long unending process that really requires repentances from those who are involved in it.